Testing the porphyrinogenicity of propofol in a primed rat model - Böhrer, Hubert; Schmidt, Heinfried; Martin, Eike; Lux, R.; Bolsen, Klaus; Goerz, Günter (British journal of anaesthesia, 1995)
We evaluated the porphyrinogenicity of propofol in a rat model. After a pilot study had been conducted to determine an optimal dose, 48 fasting male Sprague-Dawley rats were allocated randomly to six groups. The animals in groups 1-3 received saline i.p. In groups 4-6, the animals were given allylisopropylacetamide (AIA). Twelve hours later, animals in groups 1 and 4 received saline, groups 2 and 5 were given propofol 150 mg kg-1 i.p., followed by 75 mg kg-1 3 h later, and groups 3 and 6 received phenobarbitone 50 mg kg-1 i.p. and 25 mg kg-1 i.p. The animals were anaesthetized and killed 3 h after the second drug bolus and we measured the concentration of cytochrome P450, total porphyrin content and the activity of delta-aminolaevulinic acid synthase (ALAS) in the liver. Urinary delta-aminolaevulinic acid (ALA) and porphobilinogen (PBG) concentrations were measured. Analysis of variance and the t test with Bonferroni's correction were used to compare data. The hepatic cytochrome P450 concentration in the non-primed groups varied from 28.1 to 31.1 nmol g-1; administration of AIA decreased this to 20.1-20.9 nmol g-1. Total hepatic porphyrins were between 0.78 and 1.22 nmol g-1 in the non-primed groups and between 2.71 and 3.54 nmol g-1 in the AIA-primed groups. Hepatic ALAS activity was 29.2 and 35.5 nmol h-1 g-1 in groups 1 and 2. In the primed saline group, ALAS activity was measured at 134.5 nmol h-1 g-1.(ABSTRACT TRUNCATED AT 250 WORDS)
Elektronische Reproduktion der Druck-Ausgabe 13. Dezember 2017
Gesehen am 30.04.2024